The Determinants of Employee Satisfaction in Financial Services Outsourcing Companies in Indonesia - Dodi Irawanto; Achmad Sudiro; Karuniawati Putri Sentosa (International School for Social and Business Studies, 2018)
This study aims to examine the effects of organizational climate and leadership on employees' job satisfaction, mediated by psychological empowerment. The respondents in this study were all employees of financial services outsourcing companies in Surabaya. The data analysis used partial least square from 150 respondents, showing that organizational climate and leadership have positive and significant effects on job satisfaction, as well as on psychological empowerment, while psychological empowerment in turn has a positive and significant effect on job satisfaction. Similarly, psychological empowerment can significantly mediate the organizational climate's effect on job satisfaction, and psychological empowerment can significantly mediate the effect of leadership on job satisfaction.